Room temperature ethanol sensing properties of FET sensors based on ZnO nanostructures - Ekasiddh Wongrat (2018)
© 2017 Elsevier Ltd and Techna Group S.r.l. In this work, the ethanol sensing properties of field effect transistor (FET) sensors based on ZnO nanostructures were investigated at the room temperature and compared with those of based on ZnO thin film. ZnO thin film was deposited by RF magnetron sputtering. While ZnO nanostructures were prepared by a thermal oxidation technique. They were completely configured as the bottom gate FET structures. It was found that our devices exhibit the n-channel semiconductor with a drain-source current on/off ratio in order of 10 5 and 10 4 for ZnO thin film and ZnO nanostructures, respectively. In addition, the sub-threshold swing (SS) of ZnO nanostructures extremely change with ethanol supply flowed into the system. It can be seen that this SS of FET with ZnO nanostructures in air is found to be 1.5 V/decade. On the other hand, the SS of devices are achieved with the value of 1.1 and 0.7 V/decade for the ethanol concentrations of 50 and 100 ppm, respectively. The sensor response of FET sensor based on ZnO nanostructures is about 6 whereas thin film structure is about 3 at 100 ppm concentration. This suggests the sensor response improvement of FET sensors at the room temperature due to surface to volume ratio effect of nanostructures formation.